The implications of globalisation for the ECB monetary policy strategy (European Central Bank (ECB), 2021)
This paper assesses how globalisation has shaped the economic environment in which the ECB operates and discusses whether this warrants adjustments to the monetary policy strategy. The paper first looks at how trade and financial integration have evolved since the last strategy review in 2003. It then examines the effects of these developments on global productivity growth, the natural interest rate (r*), inflation trends and monetary transmission. While trade globalisation initially boosted productivity growth, this effect may be waning as trade integration slows and market contestability promotes a winner-takes-all environment. The impact of globalisation on r* has been ambiguous: downward pressures, fuelled by global demand for safe assets and an increase in the propensity to save against a background of rising inequality, are counteracted by upward pressures, from the boost to global productivity associated with greater trade integration. Headline inflation rates have become more synchronised globally, largely because commodity prices are increasingly determined by global factors. Meanwhile, core inflation rates show a lower degree of commonality. Globalisation has made a rather modest contribution to the synchronised fall in trend inflation across countries and contributed only moderately to the reduction in the responsiveness of inflation to changes in activity. Regarding monetary transmission, globalisation has made the role of the exchange rate more complex by introducing new mechanisms through which it affects financial conditions, real activity and price dynamics. Against the background of this discussion, the paper then examines the implications for the ECB's monetary policy strategy. In doing so, it asks two questions. How is the ECB's economic and monetary analysis affected by globalisation? And how does globalisation influence the choice of the ECB's monetary policy objective and instruments? ...
Keywords: E58; F42; F44; F62; F65; 330; Globalisation; monetary policy strategy; r*; inflation; productivity